Wound contact layers: The unsung heroes of burn care when utilising negative pressure wound therapy. Issue 2 (April 2023) - Lumsden, Emma; Kimble, Roy; Griffin, Bronwyn; McMillan, Catherine
Abstract: Burns care can alter the trajectory of burn re-epithelialisation. Currently, it is not known which dressings optimise wound re-epithelialisation when used in conjunction with Negative Pressure Wound Therapy (NPWT). Here we present the case of NR, an 11yoM who had two different dressing combinations (Mepitel™ and ACTICOAT™; and ACTICOAT™) applied to his wound with differing outcomes. The areas with Mepitel™ and ACTICOAT™ re-epithelialised faster than those areas with ACTICOAT™ alone. We hypothesise this to be due to a combination of increased cytotoxic effects, minimised microdeformations and increased localised trauma with dressing removal usually facilitated by Mepitel™. Further research is required; however, based on this case we advise that a porous, wound contact layer is placed beneath nanocrystalline silver dressings when utilising in conjunction with NPWT.